ANALISIS PENERAPAN METODE YANBU’A DALAM PROGRAM TAHFIDZHUL QUR’AN DI SDUT BUMI KARTINI - Soraya, Lulu' Afro'; Zumrotun, Erna (Universitas Muhammadiyah Jakarta, 2024)
The Yanbu'a method is a method/thoriqoh (book) that teaches reading and writing and memorizing the Koran quickly, easily and precisely for children and adults. This type of research is qualitative research with the aim of describing in detail the process of implementing the yanbu'a method in the tahfidzul qur'an program at SDUT Bumi Kartini. Data collected through observation, interviews, surveys and documentation methods. The results of this research show 1. The use of the Yanbu'a method in the tahfidzhul Qur'an program at UT Bumi Kartini Elementary School. 2. Supporting and inhibiting factors in the tahfidzul Qur'an program at UT Bumi Kartini Elementary School, 3. What are the solutions to the obstacles to the Yanbu method? 'a at SDUT Bumi Kartini 4. What is the impact of implementing the Yanbu'a method on students at SDUT Bumi Kartini. In reality, the Tahfidzhul Qur'an program has a good influence on students, including students becoming a source of pride for their parents and children being more responsible with the task of adding and memorizing muroja'ah. Therefore, researchers want to provide insight into effective teaching methods in the tahfidzhul Qur'an program in elementary schools, which is an important part of religious and character education.Keywords: Yanbu’a Method, Tahfidzhul Qur’an, SDUT Bumi Kartini